2003
DOI: 10.2165/00003495-200363160-00007
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Glargine

Abstract: Insulin glargine is a human insulin analogue prepared by recombinant DNA technology. Modification of the human insulin molecule at position A21 and at the C-terminus of the B-chain results in the formation of a stable compound that is soluble at pH 4.0, but forms amorphous microprecipitates in subcutaneous tissue from which small amounts of insulin glargine are gradually released. The plasma concentration versus time profile of insulin glargine is therefore relatively constant in relation to conventional human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Drug modifications have been particularly important for the delivery of insulin. For example, long-acting formulations such as insulin glargine (Lantus), a modified human insulin with pH-dependent solubility that forms microprecipitates in the subcutaneous space, and degludec (Tresiba), an acylated insulin analogue that forms high-molecular-weight complexes, were made possible via rational modifications to the structure of insulin 129,130 . In these formulations, insulin monomers are slowly released from a subcutaneous depot, thus mimicking aspects of natural host-mediated insulin secretion, reducing injection frequency and the risk of hypoglycaemia and improving glycaemic control 131 .…”
Section: Drug Modificationsmentioning
confidence: 99%
“…Drug modifications have been particularly important for the delivery of insulin. For example, long-acting formulations such as insulin glargine (Lantus), a modified human insulin with pH-dependent solubility that forms microprecipitates in the subcutaneous space, and degludec (Tresiba), an acylated insulin analogue that forms high-molecular-weight complexes, were made possible via rational modifications to the structure of insulin 129,130 . In these formulations, insulin monomers are slowly released from a subcutaneous depot, thus mimicking aspects of natural host-mediated insulin secretion, reducing injection frequency and the risk of hypoglycaemia and improving glycaemic control 131 .…”
Section: Drug Modificationsmentioning
confidence: 99%
“…The insulin then slowly dissipates from these microprecipitates, allowing it to be absorbed into the circulation. 19 …”
Section: Pharmacokinetics and Pharmacodynamics Of Glargine-100 And Glmentioning
confidence: 99%
“…While there was no clear benefit during pre-approval data of glargine over NPH, subsequent post-FDA approval studies [ Table 3 ] and their meta-analysis [ Table 4 ] did show significant benefit of glargine over NPH based mainly on hypoglycemia outcome, especially nocturnal hypoglycemia. [ 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] Some studies also showed benefit in A1c and FBS reduction compared to NPH. Finally, a CV trial of glargine, Outcome Reduction with an Initial Galrgine Intervention (ORIGIN) trial showed CV neutrality of glargine over 6.2 years.…”
Section: T He G Largine S mentioning
confidence: 99%